PENGEMBANGAN BAHAN AJAR TEMATIK BERBASIS KEARIFAN LOKAL KALIMANTAN BARAT PADA KELAS III TEMA 5 DAN 6 SD/MI - Arianton, Arianton; Mansur, Mansur; Muskania, Ricka Tesi (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2023)
This research was conducted to determine the development of thematic teaching materials based on West Kalimantan local wisdom in Class III Themes 5 and 6 of Elementary Schools/Madrasah Ibtidaiyah. To make it easier for researchers to collect data, the researcher describes the specific objectives of knowing aspects of material content, aspects of presentation of material, aspects of design and aspects of language in the process of developing teaching materials based on local wisdom of West Kalimantan. This research uses R&D (Research And Development) research using a 4-D model (Define, Design, Develop, Dessiminate). In addition, researchers also use a qualitative approach to research qualitative data. The data sources in this study are the results of the validator's assessment regarding the assessment of material content validation, material presentation validation, design validation and language validation. The results of data validation can be interpreted as follows: Validation of West Kalimantan local wisdom-based thematic teaching materials in class III themes 5 and 6 of Elementary Schools/Madrasah Ibtidaiyah by six validators. 1) The material content validator is in the criteria of "Very Valid and Not Revised" with a proportion of 88.34%. 2) Validation by the material presentation validator is in the criteria of "Very Valid and Not Revised" with a proportion of 97.14%. 3) Validation by the book design validator is in the criteria of "Very Valid and Not Revised" with a proportion of 99.61%. 4) Validation by the language validator is in the criteria of "Very Valid and Not Revised" with a proportion of 90%.